2015
DOI: 10.1007/s00066-015-0872-9
|View full text |Cite
|
Sign up to set email alerts
|

Elective pelvic versus prostate bed-only salvage radiotherapy following radical prostatectomy

Abstract: Elective WPRT for SRT may improve bRFS in patients with unfavorable risk factors. These results need to be confirmed by a prospective randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…For selected, high-risk patients, WPRT is often used to irradiate pelvic lymph nodes, which may harbor occult metastases [11, 22]. This study furthers understanding of the clinical implications of BCR after RP and the treatment effect of WPRT during SRT, confirming the results of previous studies demonstrating that WPRT (with or without ADT) can reduce the incidence of subsequent secondary biochemical relapse [11, 13]. With regard to the potential increase in toxicity following WPRT compared with PBRT in the postprostatectomy RT setting, several studies have demonstrated that the risk of developing late GI toxicity is significantly reduced with intensity modulated radiotherapy compared with three-dimensional conformal radiotherapy [15, 23, 24].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…For selected, high-risk patients, WPRT is often used to irradiate pelvic lymph nodes, which may harbor occult metastases [11, 22]. This study furthers understanding of the clinical implications of BCR after RP and the treatment effect of WPRT during SRT, confirming the results of previous studies demonstrating that WPRT (with or without ADT) can reduce the incidence of subsequent secondary biochemical relapse [11, 13]. With regard to the potential increase in toxicity following WPRT compared with PBRT in the postprostatectomy RT setting, several studies have demonstrated that the risk of developing late GI toxicity is significantly reduced with intensity modulated radiotherapy compared with three-dimensional conformal radiotherapy [15, 23, 24].…”
Section: Discussionsupporting
confidence: 79%
“…Patients subsequently underwent either PBRT or WPRT. Details of the radiation technique used have been described previously [1315]. In brief, the clinical target volume (CTV) of WPRT included prostate bed, seminal vesicle, and presacral, obturator, internal iliac, and external iliac nodal regions.…”
Section: Methodsmentioning
confidence: 99%
“…WPRT doses in recent studies ranged from 40 to 54 Gy. WPRT was associated with a bPFS benefit in some studies [26, 29, 30] while others described an association limited to subgroups [28] or found no association at all [27, 32]. The strongest but not yet fully published evidence so far in support of combining PBRT and WPRT comes from an interim analysis of the RTOG-0534/SPPORT trial which showed significantly different 5-year failure-free survival rates between PBRT, PBRT plus ADT and WPRT plus ADT arms of 71.7, 82.7 and 89.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the salvage setting, the results of RTOG 0534 (NCT00567580) comparing SRT alone versus SRT plus short-term ADT versus SRT, short-term ADT and pelvic lymph node radiotherapy are eagerly awaited. Our survey reflects the uncertainties in the use of elective radiation to the pelvic nodes [30]. Of the participating centers 43% responded that they treat the pelvis according to the presence of high-risk disease (a definition that was not uniform), the presence of pN1 or according to the extent of previous lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%